Chameleonfishes in Bangladesh: hipshot taxonomy, sibling species, elusive species, and limits of species delimitation (Teleostei: Badidae) - Kullander, Sven; Norén, Michael; Rahman, Md. Mizanur; Mollah, Abdur Rob (Zootaxa, 2019)
Five species of Badidae are reported from Bangladesh, with morphological diagnoses and mitochondrial DNA sequences (cytochrome b, cytb; and cytochrome c oxidase subunit I, coi). Dario kajal is recorded from Bangladesh for the first time with a precise locality. Badis badis is reported from several localities in central Bangladesh. Badis chittagongis is redescribed on the basis of samples from the region of Cox′s Bazar, including Maheskhali Island. Badis pallidus, new species, is described from the Sangu and Karnafuli River drainages in Bangladesh. It is most similar to B. chittagongis, but differs slightly in colouration and meristics, and is separated by 3.8% uncorrected p-distance in coi from B. chittagongis. Badis chittagongis and B. pallidus are almost identical in morphology, colour pattern and meristics, but occupy different habitats and are reciprocally allopatric. Pronounced genetic difference but similar morphology in these two species may be due to strong stabilizing selection for cryptic colouration in Badis. Badis rhabdotus is a new species from northeastern Bangladesh and adjacent Meghalaya in India. It is distinguished from congeneric species by the colour pattern, including well-defined narrow vertical bars; posterior bars curved; and meristics. Species delimitation analysis of an alignment comprising all coi sequences available from GenBank longer than 600 bp and attributed to species of Badidae (21 June 2018) plus our coi sequences and outgroup sequences of Nandus nandus, using pairwise p-distance and the computer software GMYC, ABGD, and bPTP, produced similar results. Among 103 coi sequences of Badidae, unidentified or tagged with one of 18 valid species names, uncorrected p-distance suggests 27 OTUs at 2% difference threshold; ABGD found between 15 and 55 OTUs; GMYC with single evolutionary rate 33 OTUs, with multiple evolutionary rates 32 OTUs; PTP, mPTP and bPTP 27–28 OTUs. Phylogenetic analysis based on coi and cytb sequences support previous analyses and previously proposed species groups. Inadequate recent species descriptions and many misidentifications or provisional identifications of published DNA sequences hamper progress in species-level systematics in Badis. Based on published morphological data, Badis triocellus cannot be distinguished from B. singenensis; Badis dibruensis and B. pancharatnaensis cannot be distinguished from B. badis; Badis andrewraoi, B. autumnum, B. kyanos, and B. soraya are insufficiently well distinguished from each other.